Determinant of repeat revascularization within 5 years of Percutaneous Coronary Intervention at a tertiary care hospital, Karachi: A matched case-control study. (March 2022) - Valliani, Komal; Artani, Azmina; Azam, Iqbal; Tai, Javed; Kadir, M. Masood
Abstract: Objective: To determine factors associated with repeat revascularization among adults aged 25 years and above within 5 years of first Percutaneous Coronary Intervention (PCI) at a tertiary care hospital. Methods: A matched case-control study was conducted through a hospital records review. A total of 90 cases with repeat revascularization and 180 controls without repeat revascularization were included. Data was analyzed using Multiple Conditional Logistic Regression. Results: The mean age was similar in cases and controls (60.05 ± 10.01 vs 62.20 ± 10.43 years) and sex (male: 77.8% vs. 76.1%). History of being an ever-smoker (40% vs. 25%), overweight (36.3% vs. 30.6%), and poor glycemic control (23.3% vs. 12.2%) were more among the cases than controls. However, obesity (53.7% vs. 44.3%) and pre-diabetes (16.1% vs. 7.8%) were more in controls compared to cases. Upon matching on the time of index PCI, the adjusted odds of ever smokers among patients with repeat revascularization was 2.47 times the odds of ever smokers among patients who did not undergo revascularization. Increasing stent diameter by 1 mm was found to reduce the risk of repeat revascularization by 51%. Conclusions: Smoking cessation and appropriate selection of stent diameter in patients undergoing revascularization can reduce the risk of repeat revascularization in the future. Highlights: Study assessed determinants of repeat revascularization after initial PCI from a large tertiary care hospital in Karachi. Ever smokers undergoing index PCI have 2.47 times increased risk of repeat revascularization. 1 mm increase in stent diameter reduces 51% risk of repeat revascularization. Association between smoking and repeat revascularization may be a severe problem than estimated due to the reporting bias. More effective and well-tolerated strategies are needed for smoking cessation and sustain abstinence.